Motivation and methods for altitude training in triathletes - Rance, A. G. S.; Bourrel, N.; Guezennec, C. -Y. (Science + Triathlon 2015 World Conference, 2015)
Among elite endurance athletes there is general agreement that adaptation to hypoxic training can enhance sea level performance, this is sustained by the physiological mechanisms of altitude adaptation which are :an increase of total volume of red blood cells and total haemoglobin mass, an enhancement of mitochondrial efficiency, an improvement of both muscle buffering and ability to tolerate lactic acid production. Several methods were used to obtain hypoxic adaptation. The classic "Live High-Train High" (LHTH) method has been firstly employed, but at moderate altitude elite athletes are not able to maintain the training velocities required for competitive event, so that it was proposed to Live High and Training Low (LHTL)in order to obtain the physiological benefits of altitude adaptation and conserve same training intensity at sea level. In spite of numerous studies the respective effects of these different methods remain an area of discussion. A meta-analysis conducted by Bonetti and Hopkins (2009) examining the effects of various modalities of altitude training on sea level performance provide support for classic altitude training for endurance athletes, The most interesting effect of characteristics with the natural protocols was the increase in V02max. But the data reported on triathletes, according the effect of hypoxic training on performance, were only obtained with artificial hypoxic exposure (Vallier et al. 1996., Dehnert et al. 2002, Hendriksen et al. 2003) and don`t evidence a substantial effect on aerobic capacity, it is not possible to conclude upon this basis on the interest for triathletes to perform training in natural environment at moderate altitude. To gives basis for such a training a survey was conducted with a questionnaire on a population of triathletes trained at middle altitude (1800-2000m) in natural environment. The main items were: the altitude of training, the duration, the objective, the quality of life at altitude, the effect on performance during the return at sea level.The data obtained gives information`s about the interest and motivation of triathletes for training at altitude.